A Comprehensive Analysis of the Variably Saturated Hydraulic Behavior of a Green Roof in a Mediterranean Climate. Issue 9 (25th August 2016) - Brunetti, Giuseppe; Šimůnek, Jirka; Piro, Patrizia
Abstract : Core Ideas: A comprehensive numerical analysis of hydrological processes in a green roof was conducted. The substrate of the green roof demonstrated bimodal behavior. The validated model accurately describes the hydraulic behavior of the green roof. The soil moisture governs the performance of the green roof during precipitation. Low‐impact developments (LIDs), such as green roofs, have proven to be valuable alternatives for stormwater management and hydrological restoration. Mechanistic models are reliable and accurate tools for analysis of the hydrologic behavior of LIDs, yet only a few studies provide a comprehensive numerical analysis of the hydrological processes involved and test their model predictions against field‐scale data. Moreover, more research is needed to determine the unsaturated hydraulic properties of the substrates used in LIDs. For these reasons, the aim of this study was to provide a comprehensive description of the hydrological behavior of an extensive green roof installed at the University of Calabria. The soil hydraulic properties were determined by using the simplified evaporation method. Both unimodal and bimodal soil hydraulic functions were used in the analysis. The estimated parameters were then used in the HYDRUS‐3D model to simulate a 2‐mo‐long period. Precipitation, irrigation, evaporation, and root water uptake processes were included in the numerical analysis. The values of 0.74 and 0.8 of the Nash–Sutcliffe efficiency index for the model predictions using unimodal and bimodal functions, respectively, confirmed the good agreement between the modeled and measured outflows. The bimodal model was able to both accurately reproduce the hydrographs in both dry and wet periods and account for daily fluctuations of soil moisture. Finally, the validated model was used to carry out a hydrological analysis of the green roof and its hydrological performance during the entire simulated period as well as during single precipitation events.